Characteristics of Indicators of Physical Condition and Physical Fitness among Students of Senior School Age - Таrаs Blistiv (Kazimierz Wielki University, 2017)
The article presents the results of determining the indicators of physical condition and physical fitness of schoolchildren, aged 15-16, necessary to elaborate a health and recreational activities program. To solve the research tasks, the following research methods were applied: the analysis of scientific and methodological works and documentary materials; anthropometric, physiological, pedagogical methods of research; and methods of mathematical statistics. The study involved 50 students aged 15 (33 boys and 17 girls) and 49 people aged 16 (34 boys and 15 girls). Among different indicators of the physical condition, the features of physical development, the functional state of the cardiovascular and respiratory system, and the physical fitness of children of senior school age were examined. According to the research results, the compliance between the age standards and the indicators of physical development and functional state of the cardio-respiratory system of boys and girls aged 15-16 was established. At the same time, it should be noted that there is a high variability of certain indicators between boys and girls of the senior school age. The variation coefficients have exceed 14.6%, which indicates the heterogeneity of the sample. The evaluation results of indicators of physical fitness revealed that about a quarter of senior pupils had difficulties in performing the tasks, especially those determining the level of endurance, coordination abilities, flexibility. The results obtained should be taken into account for developing a health and recreational activities program for the specified range of schoolchildren.